Pengaruh Penggunaan Model Pembelajaran Living Value Education (Lve) Terhadap Nilai Pendidikan Karakter Siswa Kelas 5 Sd Negeri 4 Purwawinangun - Rozak, Jaja Abdul; Acesta, Arrofa; Oktaviani, Ndaru Mukti (Peneliti.net, 2023)
This research is motivated by the implementation of a learning process that has not been effective in implementing the cultivation of character education in everyday life. This is proven by the fact that the character education that is instilled in schools is not implemented by students. This shows that the cultivation of character education has not achieved the target. So this research aims to determine the influence of the Living Values ​​Education (LVE) model on character education values ​​in class V of SD Negeri 4 Purwawinangun. The type of method used in research is pre-experimental. The research design used in this research is one group pre-test post-test. The data analysis technique in this research is using the t test and gain calculation. Based on the results of research and data analysis that has been carried out, the Living Values ​​Education (LVE) model influences the 18 character education values, namely Religious, Honest, Tolerant, Disciplined, Hard Working, Creative, Independent, Democracy, Curiosity, Enthusiasm Nationality, Love for the Motherland, Appreciate Achievement, Communicative, Love Peace, Love Reading, Care for the Environment, Social Care, Responsible